THE VALUES oF ISLAMIC EDUCATION IN THE IMPLEMENTATION oF RAMPANAN KAPA' IN THE MIDST oF RELIGIOUS LIFE IN THE TANA TORAJA COMMUNITY - Abdullah, Ahmad; Mansyur, Saidin; Sabae, Mahlani; Makmur, Makmur; Hasanah, Uswatun (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: The Rampanan Kapa’ tradition is a customary wedding practice among the Tana Toraja people, rooted in the Aluk Todolo belief system. This tradition carries significant philosophical and spiritual values that have evolved in the context of a multicultural community, which includes both Muslims and Christians. Purpose: The study aims to explore the philosophical meanings embedded in the Rampanan Kapa' tradition, its practice among adherents of Aluk Todolo, its adaptation among Muslims and Christians, and the Islamic educational values inherent in this tradition. Additionally, it seeks to examine the impact of the Rampanan Kapa' tradition on the socio-religious life of the multicultural Torajan community. Method: This research adopts a descriptive qualitative approach, utilizing in-depth interviews, observations, and documentation for data collection. Result: The analysis reveals that the Rampanan Kapa' tradition upholds key Islamic educational values, such as responsibility, honesty, loyalty, cooperation, and justice, while also emphasizing social and spiritual values in the context of marriage. Despite the multicultural influences, the tradition has been preserved and adapted by both Muslims and Christians as a unifying social practice. Implication: The Rampanan Kapa’ tradition not only serves as a cultural heritage but also plays a vital role in character education and fostering multiculturalism within Indonesian society. Conclusion: This study highlights the importance of integrating cultural traditions with Islamic values to strengthen socio-religious harmony in diverse communities.